A job analysis of selected health workers in a district health system in KwaZulu Natal - Part one: Job analysis of nurses in hospital settings - L.R. Uys (AOSIS, 2003)
The aim of this descriptive survey was to do a job analysis of different categories of nurses in a District Health System in order to clarify job expectations, describe current practice of nurses in hospitals and clinics and to make recommendations about skills mix in district services.